Revitalisasi Kriteria Pemimpin Qur'ani Bagi Bangsa Indonesia (Studi Penafsiran pada Ayat Kisah Nabi Sulaiman AS) - Mulyadi, Dudung; Firdaus, Muhamad Yoga (Faculty of Ushuluddin UIN Sunan Gunung Djati Bandung, 2023)
The aim of this paper is to present an ideal Qur'anic leadership model, using the perspective of the Qur'an and the interpretation of the story of the Prophet Sulaiman AS as the main source of inspiration. The writing of this work also used qualitative techniques based on literature searches and the Maudhu'i method. This paper concludes that the message of wisdom in the Al-Qur'an conveys a leadership concept that includes intellectual and spiritual capabilities, capabilities for cadre formation and good communication, good managerial capabilities, good social responsibility, and a disciplined and firm attitude. Through revitalization efforts, it is hoped that the idea of a leadership prototype from the perspective of the Qur'an will be a trigger for the birth of benefits in world life, especially in Indonesia. The weakness of this article is that it only discusses the leadership prototype of one prophet's story. In subsequent writings, this study suggests exploring more specifically the Al-Qur'an exegetical literature on leaders in order to explore more diverse and comprehensive Qur'anic leadership values as criteria for quality leaders.